Minimally Invasive Cosmetic Restoration of Teeth Associated with Open Gingival Embrasures. Descriptive Case Series - Álvaro Ferrando Cascales; Rubén Agustín Panadero; José Amengual Lorenzo; Salvatore Sauro; Antonio Mendoza Rodríguez; Raúl Ferrando Cascales; Ronaldo Hirata; David Clark (Journal of the California Dental Association)
The aim of this study is to evaluate the performance of the restorations and soft tissues at 2 years using direct composite resin with injection molding technique to solve open gingival embrasures, also known as black triangles.Materials and Method An observational study of a case series was conducted for the treatment of black triangles. The criteria evaluated in each of the restorations were: color stability, polishing, maintenance of surface gloss, staining in the tooth/restoration margins, secondary caries, radiographic appearance of the restored emergence profile, probing depth and bleeding on probing (of the restored proximal surface), presence of plaque (of the restored proximal surface), detachment, delamination, and fracture of the restoration. The following patient satisfaction criteria were evaluated using the visual analog scale (VAS): aesthetic, functional and overall satisfaction.Results A total of 36 restorations were performed in the anterior aesthetic area between canines (24 upper and 12 lower). The mechanical and biological survival rate of restorations were both 100% (95%CI: 90.3–100%). Regarding mechanical complications, there were no restorations showing secondary caries, alteration of color, staining in the tooth/restoration interface, detachment, delimitation or fracture during the entire follow-up (0%; 95%CI: 0–9.7%). Regarding biological complications, there were no restorations measuring probing depth higher than 3 mm or showing an unusual radiographic appearance during the entire follow up (0%; 95%CI: 0–9.7%).Conclusions The composite injection technique using anatomical matrices is a cost-effective, minimally traumatic, predictable, and reproducible approach to achieve anterior black triangles closure and creation of pseudopapillas.